Efficient and Parsimonious Agnostic Active Learning - Huang, Tzu-Kuo; Agarwal, Alekh; Hsu, Daniel; Langford, John; Schapire, Robert E. (Advances in Neural Information Processing Systems 28 (NIPS 2015), 2015)
We develop a new active learning algorithm for the streaming setting satisfying three important properties: 1) It provably works for any classifier representation and classification problem including those with severe noise. 2) It is efficiently implementable with an ERM oracle. 3) It is more aggressive than all previous approaches satisfying 1 and 2. To do this we create an algorithm based on a newly defined optimization problem and analyze it. We also conduct the first experimental analysis of all efficient agnostic active learning algorithms, evaluating their strengths and weaknesses in different settings.